Room temperature photocurable PEEK polymer formulations for high-performance 3D printing applications - Pal, Shibam; Gaikwad, Yogesh; Asha, S. K. (ACS Applied Engineering Materials, 2024)
Digital light processing (DLP) technology was employed to 3D print acrylate-modified poly(ether ether ketone) (PEEK). PEEK and modified PEEK (mPEEK incorporating pendant pentadecyl chain) polymers were synthesized and end-capped with urethane acrylate units. These end-modified PEEK polymers were combined with commercially available (meth)acrylic cross-linkers and photoinitiator to create photocurable resin formulations suitable for DLP 3D printing. The resulting 3D-printed parts exhibited remarkable mechanical strength, with a Young’s modulus of 2.1 GPa. This surpassed the mechanical properties of commercial acrylate resin 3D-printed parts and achieved approximately 55% of the Young’s modulus of reported commercial PEEK polymer. Notably, the thermal properties of the 3D-printed materials were impressive, including a high glass transition temperature of 140 °C and stability with only around 10% weight degradation occurring at approximately 400 °C. These innovative resins demonstrated excellent printability with high resolution, enabling the fabrication of intricate shapes, including complex dental materials by DLP 3D printing. Their versatility extends to potential applications in dentistry, automobile manufacturing, and robotics.